Ethics and Behavior of Bureaucracy In Support Strengthening Good Governance - Zura Hidayati; Geovani Meiwanda (Brawijaya University, 2022)
Bureaucrats' ethics and behavior are important aspects in referring to the implementation of good governance functions. This study aims to examine and find out whether the ethics and behavior of the apparatus is really able to provide reinforcement to the implementation of good governance. The method used in this paper is Descriptive Method with desk study study analysis, which is a study of the description of theories, concepts, or research results related to the focus of the study. The results showed that the ethics and behavior of bureaucrats play a role in shaping bureaucratic values and can strengthen the concept of governance in a government.